Strategi Guru Pendidikan Agama Islam Dalam Membangun Karakter Religius Siswa - Nurlaila Nurlaila; Ahmad Rivauzi (An-Nuha, 2022)
This study aims to describe the strategies of Islamic Religious Education teachers in teaching religious values. This type of research is qualitative with a descriptive method. This research was conducted at SMK Negeri 1 Rao Selatan. The results of this study are 1. The strategy of Islamic Religious Education teachers in teaching religious values, a. The strategy of Islamic Religious Education teachers in teaching Ta'aruf religious values ​​to students, b. The strategy of Islamic Religious Education teachers in teaching Ta'awun religious values ​​to students, c. Islamic Religious Education teachers' strategies in teaching Tasamuh religious values ​​to students. 2. The strategy of Islamic Religious Education teachers in building the religious character of students, a. Familiarize before learning begins the teacher always provides an explanation of religious attitudes, especially about morals. b. Provide examples of good behavior that can be imitated directly by students, c. Provide an explanation of the importance of having good morals. 3. Strategies of Islamic Religious Education teachers in supervising students' religious behavior, a. Strategies for implementing rules and imposing sanctions, b. Strategies for coaching outside of formal learning. 4. The driving and inhibiting factors for Islamic Religious Education teachers in building the religious character of students, a. Driving Factors, 1) Teachers at SMK Negeri 1 Rao Selatan always set a good example, 2) Fostering parents at home. b. Inhibiting factors, 1) student association factors, 2) social media factors.